2013
DOI: 10.1186/cc12813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the predictive performance of the BIG, TRISS, and PS09 score in an adult trauma population derived from multiple international trauma registries

Abstract: BackgroundThe BIG score (Admission base deficit (B), International normalized ratio (I), and Glasgow Coma Scale (G)) has been shown to predict mortality on admission in pediatric trauma patients. The objective of this study was to assess its performance in predicting mortality in an adult trauma population, and to compare it with the existing Trauma and Injury Severity Score (TRISS) and probability of survival (PS09) score.Materials and methodsA retrospective analysis using data collected between 2005 and 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
(40 reference statements)
1
30
1
3
Order By: Relevance
“…However, neither RTS nor PSS can be used when respiratory rate is missing or not recorded, and hence our models may prove to be feasible alternatives. We have previously highlighted the need for such models [24], as have Kimura et al[23] Also, our models do not require any blood parameters, for example base deficit, that models such as the Admission base deficit, International normalized ratio, and Glasgow Coma Scale (BIG) score require [39].…”
Section: Discussionmentioning
confidence: 93%
“…However, neither RTS nor PSS can be used when respiratory rate is missing or not recorded, and hence our models may prove to be feasible alternatives. We have previously highlighted the need for such models [24], as have Kimura et al[23] Also, our models do not require any blood parameters, for example base deficit, that models such as the Admission base deficit, International normalized ratio, and Glasgow Coma Scale (BIG) score require [39].…”
Section: Discussionmentioning
confidence: 93%
“…An adult trauma study made by Brockamp et al ., to compare the BIG score with other trauma scores revealed that BIG score is a good predictor of mortality in the adult trauma population,[27] and they added that in a penetrating trauma population, the BIG score performed better than in a population with blunt trauma. The BIG score has the advantage of being available shortly after admission and may be used to predict clinical prognosis or as a research tool to risk stratify trauma patients into clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of scale calibration capability is based on comparing the distributions of expected and observed mortality and carried out according to the Hosmer-Lemeshow test. Discrimination ability of prognostic scales based on their sensitivity and specificity is determined by ROC-analysis (receiver operating characteristic curve) with calculating AUC (area under curve) which illustrates predictive value of the scale [12]. When using prognostic systems with a large number of variables, the problem of data insufficiency often occurs.…”
Section: Criteria For Polytrauma and Its Severitymentioning
confidence: 99%
“…The indicators of base deficit, INR and GCS score are included in pediatric trauma BIG score which predicts unfavorable outcome of polytrauma quite accurately in adults as well, particularly, in trauma with penetrating injuries [12].…”
Section: Evaluating the Severity Of Functional Disordersmentioning
confidence: 99%
See 1 more Smart Citation